2014
DOI: 10.1016/j.juro.2013.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Anti-3-[ 18 F]FACBC Positron Emission Tomography-Computerized Tomography and 111 In-Capromab Pendetide Single Photon Emission Computerized Tomography-Computerized Tomography for Recurrent Prostate Carcinoma: Results of a Prospective Clinical Trial

Abstract: Purpose We prospectively evaluated the amino acid analogue positron emission tomography radiotracer anti-3-[18F]FACBC compared to ProstaScint® (111In-capromab pendetide) single photon emission computerized tomography-computerized tomography to detect recurrent prostate carcinoma. Materials and Methods A total of 93 patients met study inclusion criteria who underwent anti-3-[18F]FACBC positron emission tomography-computerized tomography plus 111In-capromab pendetide single photon emission computerized tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 28 publications
4
167
0
3
Order By: Relevance
“…The positivity criteria for 18 F-fluciclovine PET include persistent nonphysiologic moderate (greater than marrow) focal uptake in the prostate bed, lymph nodes, or bone (22,23).…”
Section: F-fluciclovine Pet Positivity Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The positivity criteria for 18 F-fluciclovine PET include persistent nonphysiologic moderate (greater than marrow) focal uptake in the prostate bed, lymph nodes, or bone (22,23).…”
Section: F-fluciclovine Pet Positivity Criteriamentioning
confidence: 99%
“…In this context, 18 F-fluciclovine (anti-1-amino-3-18 F-fluorocyclobutane-1-carboxylic acid), which is transported in a manner similar to glutamine, has shown promising imaging characteristics for the detection of prostate cancer recurrence. 18 F-fluciclovine PET/CT has been compared with radioimmunoscintigraphy in a randomized trial and has shown significantly higher accuracy (22,23).…”
mentioning
confidence: 99%
“…An analysis of 93 patients demonstrated an overall sensitivity, specificity, positive predictive value (PPV) and accuracy of 90.2%, 40.0%, 75.3%, 73.6% respectively (29). This series consisted of a relatively high proportion of patients who had undergone cryotherapy and brachytherapy, potentially leaving residual viable prostate tissue which may be more prone to confounding uptake due to inflammation or prostatic hypertrophy.…”
Section: Recurrent Diseasementioning
confidence: 96%
“…1] Not accounting for PSA levels or doubling times, the sensitivity, specificity, PPV, and accuracy of 18F-fluciclovine in detection of recurrent extraprostatic disease has been reported to be 55.0%, 96.7%, 95.7%, and 72.9% respectively (29). The multisite study of 596 patients by on May 10, 2018.…”
Section: Recurrent Diseasementioning
confidence: 99%
“…114 FACBC has been studied primarily in prostate cancer, in which it had higher sensitivity for tumor detection compared with 111 In-capromab pendetide (Prostascint) and 11 C-choline. 115,116 In addition, FACBC has demonstrated increased uptake in papillary renal cell carcinoma, but not in clear cell carcinoma. 117 FACBC is especially notable for the lack of associated radioactivity in the urine, which allows for better evaluation of the genitourinary tract and pelvis.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%